Analysis of factors influencing survival in patients with severe acute pancreatitis. (3rd August 2017) - Kim, Yeon Ji; Kim, Dae Bum; Chung, Woo Chul; Lee, Ji Min; Youn, Gun Jung; Jung, Yun Duk; Choi, Sooa; Oh, Jung Hwan
Abstract: Objective: Acute pancreatitis (AP) ranges from a mild and self-limiting disease to a fulminant illness with significant morbidity and mortality. Severe acute pancreatitis (SAP) is defined as persistent organ failure lasting for 48 h. We aimed to determine the factors that predict survival and mortality in patients with SAP. Methods: We reviewed a consecutive series of patients who were admitted with acute pancreatitis between January 2003 and January 2013. A total of 1213 cases involving 660 patients were evaluated, and 68 cases with SAP were selected for the study. Patients were graded based on the Computer Tomography Severity Index (CTSI), the bedside index for severity (BISAP), and Ranson's criteria. Results: The frequency of SAP was 5.6% (68/1213 cases). Among these patients, 17 died due to pancreatitis-induced causes. We compared several factors between the survivor ( n = 51) and non-survivor ( n = 17) groups. On multivariate analysis, there were significant differences in the incidence of diabetes mellitus ( p = .04), Ranson score ( p = .03), bacteremia ( p = .05) and body mass index (BMI) ( p = .02) between the survivor and non-survivor groups. Conclusions: Bacteremia, high Ranson score, DM, and lower BMI were closely associated with mortality in patients with SAP. When patients with SAP show evidence of bacteremia or diabetes, aggressive treatment is necessary. For the prediction of disease mortality, the Ranson score might be a useful tool in SAP.